Merajut Kemandirian dengan Bimbingan Produksi dan Pemasaran Syariah Batik Ecoprint pada Kelompok Wanita Keluarga Pra Sejahtera di Loktabat Utara Banjarbaru: Building Self-Reliance through Sharia-Based Production and Marketing Guidance for Ecoprint Batik in Underprivileged Women’s Groups in Loktabat Utara, Banjarbaru - Erziaty, Rozzana; Zakiyah, Zakiyah; Wahab, Abdul; Al Hadi, M. Qoshid (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The community empowerment program based on Nile tilapia cultivation using the biostimulant RAS system was expected to enhance participants' economic independence. Key challenges included limited access to information, education, and technology, alongside a lack of business management support. The program aimed to address these issues and positively impact the welfare of the disability community. Conducted under the title